Pertumbuhan Alometri Dimensi Panjang Tubuh Babi Batam Persilangan Fase Starter: The Allometric Growth Of Long Body Dimension of Batam Cross Pig Phase Starter - Andre Delima; Bernadetha Rahayu; Frandz Rumbiak Pawere (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2019)
Research was conducted at AR0-M Pig Farming in Bumi Marina, Manokwari from August to September 2017 to investigate the body length dimension of Batam Cross Pig. Eight young male Batam Cross pig at 8 month years old were measured five times. Collected data was analysed using regression curve estimation. Result showed that body length had a high potential growth. Both head and neck length had medium potential growth, length had a while tail length had a law potential growth.